A RELAÇÃO ENTRE CAPITAL HUMANO E CAPITAL PSICOLÓGICO - Oliveira, Edineide Maria de (2011)
Intangible assets received special attention from scholars in recent years in the organization context of human resource management, since theoretical proposals were developed to understand (them) and measure them. Anchored in this line of research are human capital and psychological capital. While human capital is what workers can do, the psychological capital consists of a positive mental state made up of self-efficacy, hope, optimism and resilience. The overall purpose of his study was to analyze the relationship between human capital and psychological capital. It s about a quantitative study which involved 60 workers, students of the last period of Business Administration, with a average age of 23.85 years, mostly female, single and employed. Data for the study were collected in classrooms of a private university found in the Greater ABC area , through a self-administered instrument containing an interval measure of psychological capital with 12 items, validated for Brazil, and a measure of capital human with six questions,with two to measure the experience range and four to probe education. An eletronic database was design which was submitted to descriptive analysis and correlation (Pearson s) by means of SPSS 19.0 The results revealed that participants held a human capital represented by average 4.38 years work experience and that the majority (75%) had revealed to have a maximum of five years in this topic (regard). Regarding the dimension extent of education of human capital, the majority (96.70%) had not completed any graduate course, spent between 11 and 20 years to the studies(y) (81.60%), didin t exchange shift studies (93%), while 86.70% (is) already included in their academic curriculum complementary activities in the Educational Plan of Business Administration Course attended, and 73.30% had between one and three internships. The analysis poit out a median score of psychological capital, 9 accentuated strengthened by the difficulty of the participants to recognize that they are in a phase of success at work and could see the bright side of things on the job. Investigating the relationship between human capital and psychological capital significant correlations were not found. Given these results, it s presumable that the study s participants, for the reason of being predominantly young workers who have not yet completed an undergraduate degree, although in its way of life more than 10 years devoted to studies and worked for about five years on average still do not recognize themselves, in the presence of a consistent human capital psychological. The lack of relationship observed between the two intangibles advocated by theorists as important to ensure that employees can contribute to the company in pursuit of their goals seems to reveal that more studies are still needed and developing theory to support not only the assumptions about asset intangible as well as to identify the relationship of dependence that may exist between the categories of human capital and psychological.